Rectal dose sparing and prostate immobilization using a rectal balloon in the treatment of prostate cancer with dose escalation conformal radiation therapy - Kanyike, Daniel Mukasa (My University, 2008)
ABSTRACT Objective The use of conformal radiation therapy in the treatment of carcinoma of the prostate has allowed for dose escalation and improved local control. The dose to the rectum is an important consideration in determining complication rates. This study aims to evaluate the effect of a Foleys rectal catheter balloon on the dose volume histograms to the rectum and to assess the effect of the balloon catheter on prostate gland immobilization during treatment of intermediate risk cancer of the prostate. Design and methods Ten patients with intermediate risk prostate cancer, each acting as his own control, were recruited in the study; eight patients had complete data for analysis. CT scans were done at intervals during treatment, with and without a rectal balloon filled with 30 ml of contrast. 3 pairs of CT scans for each patient were performed and were available for analysis. All patients were treated with 6-field conformal radiotherapy up to 66 Gy followed by a boost of 12 Gy in 3 fractions to the prostate using a rectal balloon and a 3- field plan. Dose volume histograms were calculated for the boost plan with and without the rectal balloon. Movements of the prostate in the superior-inferior and the anteriorposterior directions were measured with and without the balloon for each treatment. There was a slight reduction in the dose received by 1% and 2 % of the rectal volume with the balloon (55% and 52% respectively), compared to without a balloon (57% and 54.3% respectively) (p> 0.05). Results There was a non significant increase in the dose received by 50% of the rectum (p>0.05) with the use of the rectal balloon due to the rectum being pushed towards the symphysis pubis by the balloon. With the use of rectal balloon, the superior / inferior displacement of the prostate was reduced (p=0.04) and a displacement of more than 5 mm was observed in one out of eight patients. The anterior / posterior displacement of the prostate was decreased with the rectal balloon with a mean of 4 mm compared to 5 mm with no rectal balloon. This was not statistically significantly (p>0.05). However, displacement of more than 5 mm was observed in 2 patients with the rectal balloon. No grade 3 acute rectal toxicity was recorded in the 8 patients. Conclusion There was no significant change in the percentage dose received by the rectum with the use of the rectal balloon in this study. The study showed however that the rectal balloon significantly reduced prostate movement during treatment.
Keywords: prostate cancer; radiation therapy